2006
DOI: 10.1007/s00432-006-0087-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of insulin dependent NO synthesis in the impaired production of maspin in human breast cancer

Abstract: The impaired maspin production was found to be the consequence of impaired insulin induced NO production in breast cancer due to the decrease of insulin receptor binding. Restoration of NO production by aspirin can be useful for the restoration of maspin production in breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Because the increase of NO synthesis was reported to stimulate maspin synthesis in vitro, (7) we aimed to determine the effect of aspirin therapy in breast cancer patients. It was found that, within 60 min of oral ingestion of aspirin, there was an increase in plasma NO levels and the restoration of impaired plasma maspin levels to normal ranges.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Because the increase of NO synthesis was reported to stimulate maspin synthesis in vitro, (7) we aimed to determine the effect of aspirin therapy in breast cancer patients. It was found that, within 60 min of oral ingestion of aspirin, there was an increase in plasma NO levels and the restoration of impaired plasma maspin levels to normal ranges.…”
Section: Resultsmentioning
confidence: 99%
“…To determine the effect of aspirin on the synthesis of NO-induced maspin synthesis, neutrophils were prepared from blood of normal volunteers and from the breast cancer subjects at different stages of malignant disease. (8) Typically, neutrophils, reported to synthesize maspin, (7) were isolated from the blood of normal volunteers and breast cancer patients of different stages and the effect of aspirin on the synthesis of maspin was determined by in vitro translation of maspin mRNA, as described in ''Materials and Methods''. It was found that the increase in aspirin concentrations in the assay mixture that resulted in the increased synthesis of NO led to the increased synthesis of maspin (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Blood samples (20-25 mL) were collected by venipuncture using siliconized 19-gauge needles in plastic vials, and anticoagulated by gentle mixing of 1 volume of 0.13 M sodium citrate with nine volumes of blood [6]. …”
Section: Methodsmentioning
confidence: 99%